The establishment and operation of Islamic banks in Nigeria :perception study on the role of the central bank of Nigeria - Daud, Mustafa; Mohd Yussof, Ibrahim; Adewale, Abideen Adeyemi (New South Wales Research Centre Australia (NSWRCA), 2011)
Central bank (CB) in any economy is regarded as the Apex bank and the Principal stakeholder in the financial system. This is in view of the role it plays in the control, regulation and supervision of the financial institutions in the economy. Hence, the Central Bank of Nigeria (CBN) is no exception to this unique characteristics and functions. Meanwhile, the emergence of Islamic banking in various Muslim countries has continued to raise the fundamental issue of what role the CB should play in the affairs of Islamic Banks (IBs). Therefore, this study is an attempt to empirically examine the perceptions of Nigerian Muslim Youths in Malaysia on the perceived role expected of the CBN in the establishment and operation of IBs in Nigeria. This study focused on the perceptions of students in three Malaysian universities i.e. Kolej Universiti Insaniah (KUIN), Universiti Utara Malaysia (UUM) and International Islamic University Malaysia (IIUM). The sample of the study was made up of 100 questionnaires of which 85 percent were returned and usable. The data collected were subjected to statistical analysis using the SPSS version 18.0 and One-Sample and Independent-Samples t-Tests were utilized for analyses. The finding revealed that the role of the CBN in the establishment and operation of IBs in Nigeria is of no significance. This finding is however classified as Type II error because it contradicts the known theoretical and empirical evidences in the area of central banking in the world. Other findings hold that the CBN should seriously promote adequate research in IBs, the legal framework of IBs should be further strengthened and that the CBN should collaborate with the Judiciary for the establishment of Shari’ah courts to adjudicate cases on IBs.